2001
DOI: 10.1002/chin.200108291
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Acyl Phosphate Esters: Charge‐Directed Acylation and Artificial Blood

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Ltd. (Shanghai, China). N-MAP-AAs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and N-P-AAs (11)(12)(13)(14)(15)(16) were synthesized according to our published methods [15,16] . All compounds synthesized were identified by 31 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ltd. (Shanghai, China). N-MAP-AAs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and N-P-AAs (11)(12)(13)(14)(15)(16) were synthesized according to our published methods [15,16] . All compounds synthesized were identified by 31 …”
Section: Methodsmentioning
confidence: 99%
“…Acyl phosphates, such as acetyl phosphates [1,2] , aminoacyl phosphates [3,4] and aminoacyl adenylates, [5,6] are mixed anhydrides of carboxylic acids and phosphoric acid, which are involved in important biochemical transformations. Many studies have demonstrated that the mixed anhydride that functions with related enzyme is one of the principal processes of molecular activation in biochemistry, such as protein synthesis, metabolic acylating and phosphorylation.…”
Section: Introductionmentioning
confidence: 99%